2008
DOI: 10.1001/archopht.126.5.692
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Vein Occlusion and Traditional Risk Factors for Atherosclerosis

Abstract: To determine whether retinal vein occlusion (RVO) is related to systemic hypertension, diabetes mellitus, and hyperlipidemia. Methods:We systematically retrieved all studies published between January 1985 and July 2007 that compared cases with any form of RVO, including central and branch RVO, with controls. We generated pooled odds ratios (ORs) and estimates of the populationattributable risk percentages for systemic hypertension, diabetes mellitus, and hyperlipidemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

15
160
6
75

Year Published

2009
2009
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 237 publications
(278 citation statements)
references
References 32 publications
(61 reference statements)
15
160
6
75
Order By: Relevance
“…Patients with retinal vascular occlusions often present to general practitioners or ophthalmologists, and have previously been associated with various cardiovascular risk factors [7][8][9][10][11][12][13], cerebral microembolisms [14], and cardiovascular events, including stroke and myocardial infarction [11,[15][16][17]. However, another study found that risk factor prevalence differed somewhat between patients with retinal and cerebral ischemia, indicating that there might be pathogenetic differences between retinal and cerebral ischemia [18].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with retinal vascular occlusions often present to general practitioners or ophthalmologists, and have previously been associated with various cardiovascular risk factors [7][8][9][10][11][12][13], cerebral microembolisms [14], and cardiovascular events, including stroke and myocardial infarction [11,[15][16][17]. However, another study found that risk factor prevalence differed somewhat between patients with retinal and cerebral ischemia, indicating that there might be pathogenetic differences between retinal and cerebral ischemia [18].…”
Section: Introductionmentioning
confidence: 99%
“…Its prevalence changes according to studies in overall populations are from 5.2 to 16 per 1,000 [1][2][3][4] . People with end-organ damage caused by diabetes mellitus and hypertension have strongly increased risk for RVO.…”
mentioning
confidence: 99%
“…The majority of individual diagnosed with RVO defined more than one component of the systemic vascular and metabolic disease, such as the presence of Diabetes Mellitus, hyper tension and high serum lipids. Coexisting metabolic diseases are important factors for prognosis and laser treatment response [1][2][3][4][5] .There are mainly two types of RVO according to occlusion side branch retinal vein occlusion (BRVO) and central retinal vein occlusion (CRVO). In BRVO occlusion is located in the any branch of the retinal vein system, while occlusion located exactly in the central retinal vein in CRVO.…”
mentioning
confidence: 99%
See 2 more Smart Citations